2021
DOI: 10.1002/cssc.202101465
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Cobaltite: A Positive Electrode Material for Hybrid Supercapacitors

Abstract: The increased demand of energy due to the recent technological advances in diverse fields such as portable electronics and electric vehicles is often hindered by the poor capability of energy‐storage systems. Although supercapacitors (SCs) exhibit higher power density than state‐of‐the art batteries, their insufficient energy density remains a major challenge. An emerging concept of hybrid supercapacitors (HSCs) with the combination of one capacitive and one battery electrode in a single cell holds a great pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 132 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…NiCo 2 O 4 has emerged as a viable electrode for SCs because of its superior theoretical capacitance, environmentally benign features, and low cost . Furthermore, the ability to tune NiCo 2 O 4 into varied morphologies enable them to be engineered for exceptional shape-dependent properties . Despite being superior to carbon-based electrostatic double layer capacitance (EDLC) in terms of capacity, the sluggish kinetics during the faradaic reactions impede its practical use …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NiCo 2 O 4 has emerged as a viable electrode for SCs because of its superior theoretical capacitance, environmentally benign features, and low cost . Furthermore, the ability to tune NiCo 2 O 4 into varied morphologies enable them to be engineered for exceptional shape-dependent properties . Despite being superior to carbon-based electrostatic double layer capacitance (EDLC) in terms of capacity, the sluggish kinetics during the faradaic reactions impede its practical use …”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, the ability to tune NiCo 2 O 4 into varied morphologies enable them to be engineered for exceptional shape-dependent properties. 9 Despite being superior to carbon-based electrostatic double layer capacitance (EDLC) in terms of capacity, the sluggish kinetics during the faradaic reactions impede its practical use. 10 Electrode materials with improved porosity and enhanced interfacial contacts between the participating units can alter the redox kinetics resulting in improved charge−discharge characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the energy field, SCs have become one of the most important complementary energy storage devices for the commercialized lithium-ion battery as the high power supply . The transition metal oxides/sulfides such as MnO 2 , NiO, Co 3 O 4 , MnS, and MoS 2 are promising electrode materials for SCs because of their ultrahigh pseudocapacitance with abundant resources and low cost. Nanostructured NiCo 2 O 4 is the material with the most potential because its structure can be rationally designed and controlled to expose a high reactive surface area for storage of electrochemical energy . Various studies on SCs based on NiCo 2 O 4 have been reported during the past several decades. , However, the practical applications of such electrode material is still progressing slowly, and some intractable issues that need overcome remain.…”
Section: Introductionmentioning
confidence: 99%
“…The popularly investigated EDLC materials are activated carbon, graphene or reduced graphene oxide (rGO), and carbon nanotubes (CNTs) due to the high conductivity and large specific surface areas. Transition metal oxides include MnO 2 [2,5], Co 3 O 4 [6], NiO [7], CoO [8], NiCo 2 O 4 [9], Fe 2 O 3 [10], etc. that have abundant sources with high-specific capacitances.…”
Section: Introductionmentioning
confidence: 99%